2016
DOI: 10.12806/v15/i4/c1
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Theory and Practice in the Leadership Classroom: Intentional Emergence as a Modern Pedagogy

Abstract: With leadership education expanding at an unprecedented rate, there is an acute need for an evidence-based leadership pedagogy that can bridge the gap between leadership theory and student practice both in the classroom and beyond its boundaries. This paper will give an overview of the Intentional Emergence Model as a way to teach leadership to emerging adults that specifically addresses this gap between theory and practice. It will discuss the model, research and evaluation data associated with the model, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…In 2006, two instructors within the Leadership Minor at the University of Minnesota began implementing the IE model and found that initial evaluation results indicated that student satisfaction rates were higher within the two sections using the model than those sections not using the model. These IE instructors also found that a far higher percentage of students matriculated into the program from their IE sections than those in other (non‐IE) sections (Werner et al, ). As more instructors learned the IE model, program staff found that that a gap in satisfaction rates and matriculation grew between those instructors who were proficient in the IE model and those who were less skilled (who still relied heavily on using educational techniques such as lectures and case studies), with higher satisfaction and matriculation rates for those using the IE than those not using it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, two instructors within the Leadership Minor at the University of Minnesota began implementing the IE model and found that initial evaluation results indicated that student satisfaction rates were higher within the two sections using the model than those sections not using the model. These IE instructors also found that a far higher percentage of students matriculated into the program from their IE sections than those in other (non‐IE) sections (Werner et al, ). As more instructors learned the IE model, program staff found that that a gap in satisfaction rates and matriculation grew between those instructors who were proficient in the IE model and those who were less skilled (who still relied heavily on using educational techniques such as lectures and case studies), with higher satisfaction and matriculation rates for those using the IE than those not using it.…”
Section: Discussionmentioning
confidence: 99%
“…The Intentional Emergence (IE) model (Werner, ; Werner & Hellstrom, ) is a useful tool for supporting instructors in the critical reimagining of the classroom as a laboratory. Grounded in compassion and contemplative practice (Zajonc, ), skill development (Dreyfus, ; Dreyfus & Dreyfus, ), transformational learning (Mezirow, ), neuroscientific views of learning (Zull, , ), and critical leadership theory (Dugan, ; Taylor & Brownell, ), leadership instructors at the University of Minnesota have used the IE model for more than 10 years (Werner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from scaffolding content throughout the program (what is taught), there is high emphasis on scaffolding development as well (how it is taught). One of the program goals is shifting student understanding of power and responsibility away from formal authority and back to the citizens (Block, ; Heifetz, ) using intentional emergence pedagogy (Werner et al., ). Intentional emergence pedagogy is based on a combination of the case‐in‐point method which uses the classroom as the case from which to illustrate specific leadership phenomenon (Parks, ) as well as teaching practices like remaining compassionately flexible to topics students surface and engaging everyone holistically to create a shared excitement for learning (hooks, ).…”
Section: Early Leadership Educator Identity Explorationmentioning
confidence: 99%
“…Some may even facilitate portions or whole class sessions. TAs receive a structured face‐to‐face training at the beginning and middle of the semester, grounded in understanding of the intentional emergence and case‐in‐point pedagogies (Parks, ; Werner et al., ) through various intentional discussions. They are also invited to program‐sponsored instructor trainings.…”
Section: Early Leadership Educator Identity Explorationmentioning
confidence: 99%
See 1 more Smart Citation